Bioenergy and agriculture: Promises and challenges: Bioenergy and agricultural research for development - Ortiz, Rodomiro; Crouch, Jonathon H.; Iwanaga, Masa; Sayre, Ken; Warburton, Marilyn L.; Arous, José Luis; Dixon, John; Bohn, Martin; Reddy, Belum V. S.; Ramesh, S.; Wani, Suhas P. (International Food Policy Research Institute, 2006)
Converting agriculture to produce energy as well as food has become an important and well-funded global research goal as petroleum reserves fall and fuel prices rise. But the use of crop biomass—both grain and other plant parts—as a raw material for bioenergy production may compete with food and feed supplies and remove valuable plant residues that help sustain soil productivity and structure and avoid erosion. Agricultural research can mitigate these trade-offs by enhancing the biomass traits of dual-purpose food crops, developing new biomass crops for marginal lands where there is less competition with food crops, and developing sustainable livestock management systems that are less dependent on biomass residuals for feeds. Agronomists will need to define the minimum thresholds of crop residues for sustainable production in particular farming systems, especially in low-yield rainfed systems (that produce less than 5–6 metric tons of grain and straw per hectare), and to establish the level of additional residues that may be removed for other purposes, including biofuel production. Enhanced root growth offers another avenue for maintaining soil organic matter. Agricultural research can also help improve the energy efficiency of biomass crops, enhancing their value as renewable energy sources with low net carbon emissions.